Improved cycling time-trial performance after ingestion of a caffeine energy drink - Ivy, J. L.; Kammer, L.; Ding, Z.; Wang, B.; Bernard, J. R.; Liao, Y.-H.; Hwang, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2009)
Context: Not all athletic competitions lend themselves to supplementation during the actual event, underscoring the importance of preexercise supplementation to extend endurance and improve exercise performance. Energy drinks are composed of ingredients that have been found to increase endurance and improve physical performance. Purpose: The purpose of the study was to investigate the effects of a commercially available energy drink, ingested before exercise, on endurance performance. Methods: The study was a double-blind, randomized, crossover design. After a 12-hr fast, 6 male and 6 female trained cyclists (mean age 27.3 ± 1.7 yr, mass 68.9 ± 3.2 kg, and VO2 54.9 ± 2.3 ml · kg-1 · min-1) consumed 500 ml of either flavored placebo or Red Bull Energy Drink (ED; 2.0 g taurine, 1.2 g glucuronolactone, 160 mg caffeine, 54 g carbohydrate, 40 mg niacin, 10 mg pantothenic acid, 10 mg vitamin B6, and 10 µg vitamin B12) 40 min before a simulated cycling time trial. Performance was measured as time to complete a standardized amount of work equal to 1 hr of cycling at 70% Wmax. Results: Performance improved with ED compared with placebo (3,690 ± 64 s vs. 3,874 ± 93 s, p < .01), but there was no difference in rating of perceived exertion between treatments. b-Endorphin levels increased during exercise, with the increase for ED approaching significance over placebo (p = .10). Substrate utilization, as measured by open-circuit spirometry, did not differ between treatments. Conclusion: These results demonstrate that consuming a commercially available ED before exercise can improve endurance performance and that this improvement might be in part the result of increased effort without a concomitant increase in perceived exertion.